Determinação de propriedades dinâmicas do solo no campo para análise de fundações de máquinas rotativas - Ribeiro, Apolonio Tannus Filgueiras (1984)
This work aimed at the determination of dynamic soil properties for the analysis of massive-type foundations for rotating machines, with special enphasis on the model which represents the soil as a set of springs (Barkan type). With this aim, a rotating mass-type vibrator was designed and constructed. Field tests on a block-type foundation, resting on residual soil, were carried out and allowed the determination of dynamic soil properties and an evaluation of the efficiency of the vibrator. A procedure for conducting vibration-type field tests and evaluating dynamic soil properties for the design of machine foundations is put forward.